IDENTIFIKASI TINGKAT PARTISIPASI MASYARAKAT STUDI KASUS KAMPUNG LOROTAN, KELURAHAN KOTALAMA, KOTA MALANG - Amandus Jong Tallo dan Dian Ayu Paramita (Jurnal Kawistara, 2015)
Urban settlements in general are always experiencing rapid growth due to the space requirements forthe population residence. Villages as part of the urban settlements also get the impact of the problemsof urban development. Top-down system of government just make people as objects of development,so that can not reach the needs of the community. But with the bottom-up system of government,the public can determine an activity based on the needs and capabilities of its people. Therefore, theobjectives of this study were (1) to identify the forms and motifs of public participation, (2) identify thecapacity of community organizations, (3) identify the level of participation of society as a whole. Thisstudy used a qualitative descriptive analysis and used the case study method as a sample of 84 people inLorotan village, Malang city. The results show that: (1) the tendency of the usual forms of participationis social, power, thoughts and wealth. For community participation motives, motives tend to be basedon psychology, (2) based on the results of the analysis of the capacity of community organizations, thereare three organizations that have a high capacity, namely, PKK, karang taruna and community forum,(3) the level of community participation overall in character of the study area, already showing the levelof participation in the second degree participation. It is an added value in the study area are communityable to achieve the highest level of participation without government interference.